Victimless deviance: toward a classification of opposition justifications - Stylianou, Stelios (Western criminology review, 2010)
Attitudes toward victimless deviance, predominantly drug use and various sexual behaviors, are explored using data from forty-nine semi-structured in-depth interviews with participants from various social and cultural backgrounds. The central question addressed is why people oppose these behaviors. The study explores perceptions of the nature and the consequences of these behaviors and the normative principles based on which people form opinions of opposition. The results support that opposition to victimless deviance is structured based on three normative principles: the libertarian principle (opposing harm to others), the paternalistic principle (opposing harm to self), and the moralistic principle (opposing harmless wrongdoing). Arguments justifying these oppositions are presented in a classification of opposition justifications. Particular emphasis is given to moralistic oppositions.